The Mitochondrial Ca2+ Uniporter Complex (MCUC) of Trypanosoma brucei Is a Hetero-oligomer That Contains Novel Subunits Essential for Ca2+ Uptake - Guozhong Huang (American Society for Microbiology, 2018)
ABSTRACT The mitochondrial calcium uniporter complex (MCUC) is a highly selective channel that conducts calcium ions across the organelle inner membrane. We previously characterized Trypanosoma brucei’s MCU (TbMCU) as an essential component of the MCUC required for parasite viability and infectivity. In this study, we characterize its paralog T. brucei MCUb (TbMCUb) and report the identification of two novel components of the complex that we named TbMCUc and TbMCUd. These new MCUC proteins are unique and conserved only in trypanosomatids. In situ tagging and immunofluorescence microscopy revealed that they colocalize with TbMCU and TbMCUb to the mitochondria of T. brucei. Blue Native PAGE and immunodetection analyses indicated that the MCUC proteins exist in a large protein complex with a molecular weight of approximately 380 kDa. RNA interference (RNAi) or overexpression of the TbMCUc and TbMCUd genes significantly reduced or enhanced mitochondrial Ca2+ uptake in T. brucei, respectively, without affecting the mitochondrial membrane potential, indicating that they are essential components of the MCUC of this parasite. The specific interactions of TbMCU with TbMCUb, TbMCUc, or TbMCUd were confirmed by coimmunoprecipitation and split-ubiquitin membrane-based yeast two-hybrid (MYTH) assays. Furthermore, combining mutagenesis analysis with MYTH assays revealed that transmembrane helices (TMHs) were determinant of the interactions between TbMCUC subunits. In summary, our study has identified two novel essential components of the MCUC of T. brucei and defined their direct physical interactions with the other subunits that result in a hetero-oligomeric MCUC. IMPORTANCE Trypanosoma brucei causes human African trypanosomiasis and nagana in animals. The finding of a mitochondrial calcium uniporter (MCU) conserved in this parasite was essential for the discovery of the gene encoding the pore subunit. Mitochondrial Ca2+ transport mediated by the MUC complex is critical in Trypanosoma brucei for shaping the dynamics of cytosolic Ca2+ increases, for the bioenergetics of the cells, and for viability and infectivity. We found that one component of the complex (MCUb) does not act as a dominant negative effector of the channel as in vertebrate cells and that the TbMCUC possesses two unique subunits (MCUc and MCUd) present only in trypanosomatids and required for Ca2+ transport. The study of the interactions between these four subunits (MCU, MCUb, MCUc, and MCUd) by a variety of techniques that include coimmunoprecipitation, split-ubiquitin membrane-based yeast two-hybrid assays, and site-directed mutagenesis suggests that they interact through their transmembrane helices to form hetero-oligomers.